2000
DOI: 10.1074/jbc.275.11.7662
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Corepressor Alien with DAX-1 Is Abrogated by Mutations of DAX-1 Involved in Adrenal Hypoplasia Congenita

Abstract: DAX-1 is an unusual member of the nuclear hormone receptor (NHR) superfamily. Lack of DAX-1-mediated silencing leads to adrenal hypoplasia congenita and hypogonadotropic hypogonadism. Gene silencing through NHRs such as the thyroid hormone receptor (TR) is mediated by corepressors. We have previously characterized a novel corepressor, termed Alien, which interacts with TR and the ecdysone receptor but not with the retinoic acid receptors RAR or RXR. Here, we show that DAX-1 interacts with the corepressor Alien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 38 publications
2
69
0
Order By: Relevance
“…Prior work suggests that NR0B1 functions as a transcriptional repressor or corepressor 12,[21][22][23][24][25]. We found that a large number of genes were downregulated by EWS/FLI.…”
Section: Resultsmentioning
confidence: 51%
“…Prior work suggests that NR0B1 functions as a transcriptional repressor or corepressor 12,[21][22][23][24][25]. We found that a large number of genes were downregulated by EWS/FLI.…”
Section: Resultsmentioning
confidence: 51%
“…Several studies demonstrated that the DAX1 repression function is abolished by naturally occurring and artificial C-terminal DAX1 deletions (Altincicek, et al, 2000;Crawford, et al, 1998;Ito, et al, 1997;Lalli, et al, 1997;Reutens, et al, 1999;Tabarin, et al, 2000). Therefore, all of the frameshift mutations are predicted to result in a truncated DAX1 protein with disrupted carboxy-terminus thus preventing the expression of a functional DAX1 protein.…”
Section: Resultsmentioning
confidence: 99%
“…4). We compared three different DAX-1 expression constructs: (i) wildtype DAX-1, which is known to be a nuclear protein and a potent transcriptional repressor (21,23,24,27,32), (ii) the naturally occurring DAX-1 R267P mutation, which is nonrepressing possibly caused by its inability to bind the corepressors N-CoR and Alien (24,26), and (iii) a GAL4⅐DAX-1 fusion protein lacking the N-terminal receptor interaction domain but containing the repressor function within the LBD. We observed that DAX-1 WT and surprisingly also DAX-1 R267P inhibited ER␣ (Fig.…”
Section: Fig 2 Analysis Of Dax-1 Interaction Domains With Ers In VImentioning
confidence: 99%